Breeding population increase and range expansion of the Great Crested Grebe Podiceps cristatus in southeastern Norway - Dale, Svein (Ornis Norvegica, 2020)
The Great Crested Grebe Podiceps cristatus is listed as near-threatened on the Norwegian red list due to small population size, estimated in 2015 at 220–380 pairs. Population size is considered to be stable. Approximately one quarter of the population (50–100 pairs) is thought to occur in Oslo and Akershus, but this estimate is not based on detailed data, and the only previous systematic estimate was 90–100 pairs in 13 sites in 1982. In 2018, I conducted a comprehensive survey of all known and potential breeding sites to assess current population size in Oslo and Akershus. I recorded 233 pairs in 34 sites, suggesting a large increase in population size. To analyse the population increase in more detail, I collected all known records of Great Crested Grebes during the breeding season for the period 1995–2018. Analyses confirmed that there has been a strong increase, at a yearly rate of 4.2%. The increase was both due to increases in already established populations (69% of total increase), and establishment of new sites (31%). New sites were colonised in particular the last 10–15 years, and new sites were located gradually further away from the sites that were already used in 1982, indicating continuous range expansion. New sites were also located in smaller, less nutrient-rich lakes at higher elevations, perhaps indicating occupation of lower quality sites that could limit further population increase. Similar population increases have also occurred in other parts of the distribution range of Great Crested Grebes in Norway, and I present a new population size estimate for Norway at 531–634 pairs. Hence, the species no longer qualifies for red listing, and one may consider to downlist the species to least concern. Cover photo: A pair of Great Crested Grebes with chicks. Photo: Frode Falkenberg.